(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The aim of the research was to prepare an educational curriculum according to the (SAMR ) model in the development of motor flexibility and learning the abassian grip in the wrestling game and identify the impact of the prepared curriculum, the researcher also used the experimental curriculum for the two equal groups and the research sample reached (153) male and female students of the University of Israel/ Faculty of physical education and Sports Sciences, the third stage in 2023-2024 and the percentage reached (59.4) males distributed equally between the two groups and the sample was selected in a random dividing them into (25) students of the experimental group and (25) students of the control group, the researcher concluded that there is a positive effect of the educational curriculum in improving the experimental group The researcher recommends that the educational curriculum should use the SAMR model in order to develop flexibility and learn grabs in the wrestling game, as well as it is necessary to use modern technology integration models as well as the use of technological innovations of tools in the educational process that help teachers to use them for teaching in physical education